Low-density hollow glass microspheres, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202611128763.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,空心玻璃微珠在有机树脂应用过程中,与现有的原位聚合聚氨酯工程材料制备工艺适配性有待进一步提高;如引入空心玻璃微珠,聚氨酯进行原位聚合时,可能会造成聚氨酯爆聚、反应无法控制等现象
[0024] Therefore, in the above-mentioned technical solution provided by the present invention, high-temperature melting and vitrification homogenization are first employed to ensure high stability of the glass composition and viscosity, avoiding spherical defects caused by uneven raw materials; through the coating modification step, the silane modifier and composite foaming agent are uniformly coated on the surface of the glass powder particles, improving the surface activity of the modified glass powder, reducing shriveled spheres and fragmentation, and increasing the floating rate; after washing and sieving, the true density of the low-density hollow glass microspheres obtained is 0.2100-0.2500 g/cm³. 3 Furthermore, the strength is not less than 8 MPa when the volumetric breakage rate reaches 20%, the particle size D90 is 30-55μm, and the pH is 7.0-9.5; therefore, this low-density hollow glass microsphere can be used as a filler in the in-situ polymerization of polyurethane. Moreover, it has good compatibility with existing polyurethane in-situ polymerization processes, can effectively avoid phenomena such as explosive polymerization, reduce the production cost of polyurethane engineering materials, and broaden the application scenarios.
Smart Images

Figure CN122916407A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic non-metallic functional materials technology, and particularly relates to a low-density hollow glass microsphere, its preparation method and application. Background Technology
[0002] Hollow glass microspheres are inorganic functional microsphere materials characterized by their closed, hollow interior, high sphericity, low true density, moderate strength, and excellent chemical stability. Due to their lightweight, heat insulation, sound insulation, low dielectric constant, and good flowability, they are widely used in solid buoyancy materials, building reflective thermal insulation coatings, low-density cement slurry for oil fields, deep-sea engineering materials, lightweight composite materials, 5G communications, adhesives, and polymer-modified fillers. With the development of the materials industry, the goal is to develop a microsphere with a true density of 0.2100-0.2500 g / cm³. 3 Low-density hollow glass microspheres with a particle size D90 below 55μm, which combine lightweight and structural stability, are one of the important research directions for hollow glass microspheres as core functional fillers for high-end engineering materials.
[0003] However, the compatibility of hollow glass microspheres with existing in-situ polymerization processes for polyurethane engineering materials in organic resin applications needs further improvement. For example, introducing hollow glass microspheres during in-situ polymerization of polyurethane may cause phenomena such as polyurethane burst polymerization and uncontrollable reactions. To address this issue, existing technologies typically involve pre-preparing polyurethane prepolymers, then drying and sealing the powder before adding it to the prepolymer. This increases the production cost of polyurethane engineering materials, hindering their widespread application. Furthermore, conventional low-density hollow glass microspheres also suffer from insufficient strength, leading to sphere breakage in applications such as adhesives.
[0004] In addition, the traditional spray granulation method for preparing low-density hollow glass microspheres has problems such as large fluctuations in true density, uneven foaming, easy breakage, and low yield, which increases the production cost of low-density hollow glass microspheres. Summary of the Invention
[0005] In view of this, one of the main objectives of this invention is to provide low-density hollow glass microspheres that combine low density and high strength. Furthermore, their application in the in-situ polymerization process of polyurethane can effectively avoid phenomena such as explosive polymerization and uncontrollable reactions, thereby reducing the production cost of polyurethane engineering materials and broadening their application scenarios. To achieve this objective, the technical solution of this invention is: a low-density hollow glass microsphere with a true density of 0.2100-0.2500 g / cm³. 3 The particle size D90 is no more than 55 μm, the pH is 7.0-9.5, and the compressive strength is not less than 8 MPa. Here, "compressive strength" as used in this invention refers to the pressure exerted on the low-density glass microspheres when the volume breakage rate reaches 20%.
[0006] Preferably, the particle size D90 of the low-density hollow glass microspheres is 30-55 μm.
[0007] More preferably, the pH of the low-density hollow glass microspheres is 7.0-8.5, which further avoids phenomena such as explosive polymerization and uncontrollable reaction during the in-situ polymerization of polyurethane, ensuring the normal progress of the reaction, thereby promoting the application of microspheres in in-situ polymerized polyurethane engineering materials, reducing the production cost of polyurethane engineering materials, and effectively broadening the application scenarios of glass microspheres.
[0008] A second objective of this invention is to provide a method for preparing the aforementioned low-density glass microspheres, which features good pH stability, good batch stability, and high yield of the target product. To achieve this objective, the present invention provides the following technical solution:
[0009] A method for preparing the above-mentioned low-density hollow glass microspheres includes the following steps:
[0010] Raw material mixing and vitrification homogenization: First, the glass powder raw materials are uniformly mixed, then subjected to high-temperature melting and vitrification treatment, and then crushed and pulverized to obtain homogenized glass powder with a particle size D90 of 20-35μm;
[0011] Coating modification: The homogenized glass powder is coated and modified using a surface coating modifier, so that the surface coating modifier is uniformly coated on the surface of the homogenized glass powder to obtain modified glass powder; wherein, the surface coating modifier includes a composite foaming agent accounting for 0.6-0.9% of the mass of the homogenized glass powder and a silane modifier accounting for 0.3-0.8% of the mass of the homogenized glass powder, and the composite foaming agent includes calcium carbonate, sodium carbonate, sodium sulfate and sodium nitrate in a mass ratio of 6-8 : 5-8 : 2-3 : 2-3;
[0012] High-temperature foaming into spheres: The modified glass powder is subjected to high-temperature foaming into spheres to obtain original hollow glass microspheres;
[0013] Cleaning and sieving: The original hollow glass microspheres are first cleaned with a cleaning agent and then sieved to obtain the low-density hollow glass microsphere product; wherein, the cleaning agent is deionized water or an acid solution with a concentration of 2-3%.
[0014] To fully achieve vitrification homogenization, the high-temperature melting vitrification treatment method in the raw material mixing and vitrification homogenization steps includes: melting and mixing uniformly mixed glass powder raw materials at 1400℃-1500℃ to form a transparent glass liquid with uniform composition and stable viscosity; and subjecting the glass liquid to water quenching and rapid cooling treatment to obtain glass clinker.
[0015] To further improve the yield of the target product, the crushing and pulverizing process in the raw material mixing and vitrification homogenization steps includes: coarsely crushing the glass clinker to obtain coarse glass clinker with a particle size of 200-300μm; and then using wet ball milling to obtain the vitrified homogenized powder.
[0016] In one specific embodiment, the glass powder raw material comprises, by mass parts: 60.0-70.0 parts quartz powder, 10-20 parts borax, 8-15 parts calcium carbonate, 10.0-15.0 parts sodium carbonate, 2.0-4.0 parts sodium sulfate, and 1.0-2.0 parts sodium nitrate.
[0017] To improve batch stability of product performance and target product yield, the coating modification step includes: simultaneously spraying a silane modification solution and a composite foaming solution with a concentration of 20 wt%-25 wt% onto the glass powder under high-speed stirring at 800-1000 r / min, drying it, and obtaining modified glass powder with a moisture content of no more than 0.22%; wherein, the silane modification solution is prepared by uniformly mixing the silane modifier and alcohol at a mass ratio of 1:(3-5); the composite foaming solution is prepared by uniformly mixing the composite foaming agent and water; thereby uniformly coating the surface of the glass powder particles with the silane modifier and the composite foaming agent.
[0018] To minimize powder agglomeration, improve batch stability of product performance, and increase the yield of target product while ensuring the strength and other properties of low-density hollow glass microspheres, the coating modification step includes: placing the glass powder in a high-speed disperser and stirring it; simultaneously spraying the silane modification solution and the composite foaming solution into the high-speed disperser at 85-95℃; after spraying, drying and stirring at 110-120℃ for 30-60 min to obtain the modified glass powder.
[0019] To ensure good bonding between the glass powder and the composite foaming agent, the silane modifier is at least one of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, glycidoxypropyltrimethoxysilane, and glycidoxypropyltriethoxysilane.
[0020] To further ensure the yield, the high-temperature foaming and spheroidizing step includes: continuously feeding the modified glass powder into a high-temperature spheroidizing furnace, and passing it through a flame at 1300-1400℃ at a speed of 30-50 m / s in an air atmosphere to form the original hollow glass microspheres.
[0021] To further ensure the pH stability of the product and reduce the pH, the cleaning and sieving steps include: first, mixing the original hollow glass microspheres with a cleaning agent at a weight ratio of 1:5-7 and stirring for 30-60 minutes to achieve a pH of 7.0-9.5 on the surface of the hollow glass microspheres; then filtering and drying; and finally sieving to obtain the finished low-density hollow glass microspheres. Preferably, the cleaning agent is water or a 2-3% acid solution.
[0022] A third objective of this invention is to provide an application of the aforementioned low-density hollow glass microspheres in the preparation of polyurethane engineering materials.
[0023] Furthermore, the low-density hollow glass microspheres are used as fillers in the in-situ polymerization of polyurethane. The in-situ polymerization temperature is 65-90 °C.
[0024] Therefore, in the above-mentioned technical solution provided by the present invention, high-temperature melting and vitrification homogenization are first employed to ensure high stability of the glass composition and viscosity, avoiding spherical defects caused by uneven raw materials; through the coating modification step, the silane modifier and composite foaming agent are uniformly coated on the surface of the glass powder particles, improving the surface activity of the modified glass powder, reducing shriveled spheres and fragmentation, and increasing the floating rate; after washing and sieving, the true density of the low-density hollow glass microspheres obtained is 0.2100-0.2500 g / cm³. 3 Furthermore, the strength is not less than 8 MPa when the volumetric breakage rate reaches 20%, the particle size D90 is 30-55μm, and the pH is 7.0-9.5; therefore, this low-density hollow glass microsphere can be used as a filler in the in-situ polymerization of polyurethane. Moreover, it has good compatibility with existing polyurethane in-situ polymerization processes, can effectively avoid phenomena such as explosive polymerization, reduce the production cost of polyurethane engineering materials, and broaden the application scenarios. Attached Figure Description
[0025] Figure 1 This is a microscope image of the low-density hollow glass microspheres prepared in Example 3 of the present invention. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0027] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0028] In this invention, unless otherwise specified and / or stated, all numerical values involving component amounts are "mass". Unless otherwise specified, the terminology used in this invention are common terms in the relevant field. Unless otherwise specified, the preparation processes, testing methods, etc., used in the various embodiments are conventional methods well known to those skilled in the art, and the raw materials and equipment used can be obtained from publicly available commercial sources.
[0029] To promote the low-cost application of low-density hollow glass microspheres in high-end engineering materials such as in-situ polymerized polyurethane for rail transportation, building adhesives, and coatings, and to avoid or reduce the increased costs caused by the breakage of glass microspheres during their application, the first objective of this invention is to provide a low-density hollow glass microsphere that combines low density and high strength. To achieve this objective, the invention specifically adopts the following implementation scheme:
[0030] A type of low-density hollow glass microsphere with a true density of 0.2100-0.2500 g / cm³. 3 The low-density hollow glass microspheres have a pH of 7.0-9.5 and a compressive strength of not less than 8 MPa. Preferably, the particle size D90 of the low-density hollow glass microspheres is 30-55 μm. More preferably, the pH of the low-density hollow glass microspheres is 7.0-8.5, which further avoids phenomena such as explosive polymerization and uncontrollable reaction when the microspheres are used in in-situ polymerization of polyurethane, thereby promoting the application of microspheres in in-situ polymerized polyurethane adhesives and coatings for rail transportation and construction.
[0031] The second objective of this invention is to address the problems of large true density fluctuations, uneven foaming, easy breakage, low yield, and poor batch stability associated with traditional spray granulation methods for preparing low-density hollow glass microspheres. This invention first involves mixing and homogenizing raw materials to produce glassy powder, then modifying the homogenized powder with a specialized surface coating modifier. Finally, the powder is foamed into spheres at high temperature, washed, and sieved, achieving a stable true density of 0.2100-0.2500 g / cm³. 3 Preparation of low-density hollow glass microspheres with a pH value between 7 and 9.5, while also considering strength. The specific implementation scheme of this invention is as follows:
[0032] A method for preparing low-density hollow glass microspheres includes steps such as raw material mixing and vitrification homogenization, coating modification, high-temperature foaming into spheres, and washing and sieving. The specific methods for each step are as follows:
[0033] The raw material mixing and vitrification homogenization steps include: weighing 60.0-70.0 parts of quartz powder, 10-20 parts of borax, 8-15 parts of calcium carbonate, 10.0-15.0 parts of sodium carbonate, 2.0-4.0 parts of sodium sulfate, and 1.0-2.0 parts of sodium nitrate according to the mass ratio; and mixing them evenly in a high-efficiency mixer to obtain a uniformly mixed glass powder raw material; and feeding the glass powder raw material into a high-temperature glass melting furnace, where it is held at 1400-1500℃ for 8- For 10 hours, the raw materials are fully melted and homogenized to form a transparent glass melt with uniform composition and stable viscosity. The glass melt is then rapidly cooled by water quenching to form a bubble-free glass clinker with uniform composition, achieving homogenization of the glass system network structure and providing a stable foundation for subsequent spheroidization and foaming. The glass clinker is then coarsely crushed by a jaw crusher to obtain coarse glass clinker with a particle size of 200-300 μm. The coarse glass clinker is then ball-milled in a planetary ball mill for 60-120 minutes to initially refine the powder, obtaining a vitrified homogenized slurry with a solid content of 30%-50%. This slurry is then dried at 130-150℃ for 4-5 hours to obtain homogenized glass powder with a particle size D90 of 20-35 μm, preparing for subsequent coating modification.
[0034] The coating modification steps include: preparing a composite foaming agent into a composite foaming solution with a concentration of 20 wt%-25 wt% at 30℃-35℃; mixing a silane modifier and alcohol at a weight ratio of 1:(3-5) to obtain a silane modified solution; placing the homogenized glass powder in a high-speed disperser with a rotation speed of 800-1000 r / min and starting stirring; simultaneously spraying the silane modified solution and the composite foaming solution into the high-speed disperser at 85-95℃, wherein the content of the composite foaming agent in the composite foaming solution accounts for 0.6-0.9% of the mass of the homogenized glass powder, and the content of the silane modifier in the silane modified solution accounts for 0.3-0.8% of the mass of the homogenized glass powder; after spraying, continuing to stir and dry at 110-120℃ for 30-60 min to obtain modified glass powder with a moisture content not exceeding 0.22 wt%. Drying under stirring conditions can further reduce or avoid local agglomeration and uneven moisture content during the drying process, which is beneficial to improving the pelleting rate and ensuring the stability of product batches.
[0035] The main purpose of the coating modification step is to modify the homogenized glass powder to improve its dispersibility and minimize agglomeration. In this step, the silane modifier primarily introduces the composite foaming agent onto the surface of the homogenized glass powder, ensuring that all foaming agents are fully and uniformly coated on the powder surface, thus enhancing the bond between the composite foaming agent and the glass powder surface. Consequently, during the subsequent foaming and spherical formation process, the composite foaming agent generates gas on the modified glass powder surface, creating a certain pressure, which in turn increases the flocculation rate of the low-density hollow glass microspheres, reduces their true density, and increases the yield of the target product. Therefore, if too much composite foaming agent is coated on the surface of the glass powder, it will cause excessive subsequent gas generation, which will have a counterproductive effect, such as causing excessive inward gas pressure and resulting in sphere breakage. If too little foaming agent is coated, it will be difficult to activate the corresponding function. Therefore, the silane modifier coated on the surface of the glass powder accounts for 0.3-0.8% of the mass of the homogenized glass powder, and the composite foaming agent accounts for 0.6-0.9% of the mass of the homogenized glass powder. After stirring and drying, the moisture content of the modified glass powder is made not more than 0.22 wt%, which can effectively avoid or reduce agglomeration caused by moisture, and is conducive to ensuring the batch stability and sphericity of the subsequent microsphere products. Preferably, it is at least one of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, glycidyl etheroxypropyltrimethoxysilane, and glycidyl etheroxypropyltriethoxysilane. The composite foaming agent comprises calcium carbonate, sodium carbonate, sodium sulfate, and sodium nitrate in a mass ratio of 6-8: 5-8: 2-3: 2-3.
[0036] The high-temperature foaming and spheroidizing step includes: continuously feeding the modified glass powder into a high-temperature spheroidizing furnace, and passing it through a flame at a high speed of 30-50 m / s at 1300-1400℃ in an air atmosphere. The modified glass powder softens and melts at high temperature, and the internal foaming agent decomposes to generate gas to form a closed hollow structure, thus completing spheroidizing and foaming to obtain the original hollow glass microspheres.
[0037] The washing and sieving steps include: mixing the raw hollow glass microspheres with water or a 2-3% acid solution at a mass ratio of 1:5-7, stirring at 80-120 r / min for 30-60 min, followed by filtration and drying; and then sieving to obtain the low-density hollow glass microsphere product. The true density of this low-density hollow glass microsphere is stably controlled at 0.2100-0.2500 g / cm³. 3 Furthermore, the strength is not less than 8 MPa when the volumetric breakage rate reaches 20%, the particle size D90 is 30-55 μm, and the pH is 7.0-9.5.
[0038] The original hollow glass microspheres are washed with a 2-3% acid solution to bring their pH to 7.0-8.5, resulting in a final low-density hollow glass microsphere product with a pH of 7.0-8.5. Preferably, the acid solution is a 2-3% aqueous acetic acid solution.
[0039] A third objective of this invention is to provide an application of the aforementioned low-density hollow glass microspheres in the preparation of in-situ polymerized polyurethane engineering materials. Preferably, the in-situ polymerized polyurethane engineering materials include waterproof coatings, adhesives, etc., and can be used in the fields of rail transportation and construction.
[0040] Furthermore, the low-density hollow glass microspheres are used as fillers in the in-situ polymerization of polyurethane. The in-situ polymerization temperature is 65-90 ℃; this effectively avoids phenomena such as explosive polymerization and uncontrollable reactions during the polymerization process, ensuring the normal progress of the reaction, reducing the production cost of in-situ polymerized polyurethane engineering materials, and effectively broadening the application fields of glass microspheres.
[0041] The technical solution to be protected by the present invention will be further explained and illustrated below through specific embodiments.
[0042] Sample testing methods for each embodiment and comparative example:
[0043] (1) pH test method for microbead samples: The microbead samples were dried at 105℃ for 2 h, cooled to room temperature and weighed 10.00 g; pure water was boiled for 5 min to remove CO2, cooled to 25℃ and 90 g was taken; the dried and cooled microbeads and the boiled pure water were mixed and stirred for 10 min and allowed to stand for 5 min, and the pH value of the supernatant was tested using a pH tester (PHSJ-3F type).
[0044] (2) Particle size D90 test: Disperse the microbead sample evenly in deionized water and test according to the national standard GB / T19077-2016. The particle size analyzer can be Malvern MASTERSIZER3000.
[0045] (3) True density: The true density was tested according to the national standard GB / T 40401-2021 using a true density meter (Micromeritics Accupy C1350) and the gas volume displacement method.
[0046] (4) Compressive strength: The test was conducted in accordance with enterprise standard Q / SLT 002-2025 "Test Method for Isostatic Compressive Strength of Hollow Glass Microspheres". The main steps include:
[0047] 1) Sample preparation: Weigh 10-30g of sample.
[0048] 2) True density test under normal pressure: Take 0.5-10g of the prepared sample and use a true density meter to test the true density of the unpressurized sample and record it as ρ0.
[0049] 3) Test of the wall density of hollow glass microspheres: Take 1-10g of dried sample and place it in a corundum mortar, grind it thoroughly (the true density of the sample after grinding should be no less than 2.30g / cm³). 3 (i.e., thoroughly ground), the true density of the ground sample is measured using a true density meter and recorded as ρ. g .
[0050] 4) Test of true density after applying isostatic pressure: Take 0.5-10g of dried sample and put it into a sample bottle; place the sample bottle into the pressure test chamber, seal the pressure test chamber, start the equipment and slowly fill it with nitrogen to pressurize it. After reaching the set pressure, maintain the pressure for no less than 180s, open the pressure relief valve, release the pressure to normal pressure, open the pressure test chamber, and take out the sample bottle; use the same true density meter to test the true density of the sample after pressurization and record it as ρ1. The model of the pressurizing instrument is MGU-D75-2-1600(100)-E.
[0051] 5) Calculation and representation of results
[0052] The volume breakage rate (r) of the sample is calculated according to formula (1), and the result is expressed as a percentage:
[0053] ;
[0054] In formula (1):
[0055] r: Volumetric breakage rate under isostatic pressure; ρ0: Actual density of hollow glass microspheres under normal pressure, in g / cm³. 3 ρ1: The actual density of hollow glass microspheres after pressure application, in g / cm³ 3 ;ρ g The true density of the hollow glass microsphere wall, in g / cm³. 3 .
[0056] Example 1
[0057] This embodiment provides a low-density hollow glass microsphere and its preparation method, which includes the following steps:
[0058] Raw material mixing and vitrification homogenization: Weigh out 60.0 parts quartz powder, 20 parts borax, 15 parts calcium carbonate, 10.0 parts sodium carbonate, 3.0 parts sodium sulfate, 1.5 parts sodium nitrate, and modifier a according to the mass ratio. Mixed glass raw materials were obtained by adding 0.6% of the molten powder mass and 0.3% of the silane modifier to the molten powder mass. The mixed glass raw materials were fed into a high-temperature glass melting furnace and held at 1480℃ for 10 hours to fully melt and homogenize the glass raw materials, forming a transparent glass melt with uniform composition and stable viscosity. The glass melt was then rapidly cooled by water quenching to form glass clinker without bubbles and with uniform composition. The glass clinker was coarsely crushed by a jaw crusher to obtain coarse glass clinker with a particle size D90 of 283μm. The coarse glass clinker was then ball-milled in a planetary ball mill at a speed of 50r / min, with a weight ratio of coarse glass to 2-3mm zirconium beads of 1:4, for 60min to initially refine the powder, obtaining a vitrified homogenized slurry with a solid content of 40%. The slurry was then dried at 130℃ for 5h to obtain homogenized glass powder with a particle size D90 of 35μm.
[0059] Coating modification: A composite foaming agent is prepared into a 20 wt% composite foaming solution at 30°C, wherein the composite foaming agent is composed of calcium carbonate, sodium carbonate, sodium sulfate, and sodium nitrate in a mass ratio of 6:8:3:3; a silane modifier is mixed with alcohol at a weight ratio of 1:4 to obtain a silane modified solution; the homogenized glass powder is placed in a high-speed disperser and stirred, and the silane modified solution and the composite foaming solution are simultaneously sprayed into the modification vessel at 90°C, wherein the content of the composite foaming agent in the composite foaming solution accounts for 0.6% of the mass of the homogenized glass powder, and the content of aminopropyltriethoxysilane in the silane modified solution accounts for 0.3% of the mass of the homogenized glass powder. After spraying, the mixture is stirred and dried at 120°C for 30 min to obtain modified glass powder with a moisture content of no more than 0.22 wt%;
[0060] High-temperature foaming and spheroidization: The modified glass powder is continuously fed into a high-temperature spheroidizing furnace and passes through a flame at a high speed of 30 m / s at 1300°C in an air atmosphere. The modified glass powder softens and melts at high temperature, and the internal foaming agent decomposes to generate gas to form a closed hollow structure, thus completing spheroidization and foaming, and obtaining the original hollow glass microspheres.
[0061] Washing and sieving: The raw hollow glass microspheres and deionized water were mixed at a mass ratio of 1:5 and stirred at 80 r / min for 30 min, followed by filtration and drying. The low-density hollow glass microspheres were then sieved to obtain the final product, with a yield of 80%. The true density of the low-density hollow glass microspheres was 0.2102 g / cm³. 3The compressive strength is 8.3 MPa, D90 is 55 μm, and pH is 9.5 when the volume breakage rate reaches 20%.
[0062] Example 2
[0063] This embodiment provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main differences are as follows, while the remaining steps and process parameters are the same:
[0064] Raw material mixing and vitrification homogenization: The glass raw materials include 65 parts quartz powder, 13 parts borax, 12 parts calcium carbonate, 13.0 parts sodium carbonate, 2.0 parts sodium sulfate, and 1.0 parts sodium nitrate; the particle size D90 of the coarse glass clinker is 239 μm; the solid content of the vitrification homogenization slurry is 45%, and the particle size D90 of the slurry is 20 μm.
[0065] Coating modification: The composite foaming agent accounts for 0.9% of the mass of the homogenized glass powder, and the silane modifier accounts for 0.8% of the mass of the homogenized glass powder. The composite foaming agent is composed of calcium carbonate, sodium carbonate, sodium sulfate, and sodium nitrate in a mass ratio of 8:5:3:2. The silane modifier is glycidyl etheroxypropyltriethoxysilane, which is mixed uniformly with alcohol at a weight ratio of 1:5. High-temperature foaming into spheres: The modified glass powder is passed instantaneously through a flame at a high speed of 50 m / s at 1380℃ to obtain original hollow glass microspheres.
[0066] Cleaning and drying: The method was basically the same as in Example 1, except that deionized water was replaced with a 3% acetic acid solution to obtain low-density hollow glass microspheres with a true density of 0.2499 g / cm³. 3 The compressive strength was 17.6 MPa, the D90 was 30 μm, and the pH was 7.8 when the volumetric breakage rate reached 20%; and the product yield was 83%.
[0067] Example 3
[0068] This embodiment provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main differences are as follows, while the remaining steps and process parameters are the same:
[0069] Raw material mixing and vitrification homogenization: The glass raw materials include 70.0 parts of quartz powder, 10 parts of borax, 8 parts of calcium carbonate, 15.0 parts of sodium carbonate, 4.0 parts of sodium sulfate, and 2.0 parts of sodium nitrate; the particle size of the coarse glass clinker is 300μm; the solid content of the vitrification homogenization slurry is 50%, and the particle size D90 is 28μm.
[0070] Coating modification: The composite foaming agent is 0.8% of the mass of the homogenized glass powder and the silane modifier is 0.6% of the mass of the homogenized glass powder. The composite foaming agent is composed of calcium carbonate, sodium carbonate, sodium sulfate and sodium nitrate in a mass ratio of 7:6:2:2. The silane modifier is glycidyl etheroxypropyltrimethoxysilane, which is mixed with alcohol in a weight ratio of 1:3.
[0071] High-temperature foaming into spheres: Modified glass powder is passed through a flame at 1400℃ at a high speed of 40 m / s to obtain original hollow glass microspheres;
[0072] Cleaning and drying: The method was basically the same as in Example 1, except that deionized water was replaced with a 2% acetic acid solution to obtain the desired result. Figure 1 The low-density hollow glass microspheres shown have a true density of 0.2195 g / cm³. 3 The compressive strength was 10.3 MPa, the D90 was 42 μm, and the pH was 8.3 when the volumetric breakage rate reached 20%; and the product yield was 79%.
[0073] I. The Influence of Glass Homogenization
[0074] Comparative Example 1 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the steps of raw material mixing and vitrification homogenization, the melting temperature is 1200-1250℃ and the time is 6h; the remaining steps and process parameters are the same, and a true density of 0.2106 g / cm³ is finally obtained. 3 Low-density hollow glass microspheres: true density 0.2106 g / cm³ 3 The compressive strength was 6.1 MPa, D90 was 61 μm, and pH was 10.3 when the volumetric breakage rate reached 20%; and the product yield was 17%. Compared with Example 1, hollow glass microspheres of the same true density showed larger particle size, lower compressive strength, and higher pH value in Comparative Document 1; therefore, the vitrification homogenization melting process has a significant impact on the yield of the target product.
[0075] II. The Influence of Coating Modification
[0076] (1) Effect of compound foaming agent and its content
[0077] Comparative Example 2 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the coating and modification step, the concentration of the composite foaming solution is 20%, and the composite foaming agent accounts for 0.3% of the mass of the homogenized glass powder; the remaining steps and process parameters are the same, and the final true density is 0.2187 g / cm³.3 The yield of the low-density hollow glass microspheres was 53%, and the particle size D90 was 59 μm.
[0078] Comparative Example 3 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the coating and modification step, the concentration of the composite foaming solution is 20%, and the composite foaming agent accounts for 1.0% of the mass of the homogenized glass powder; the remaining steps and process parameters are the same, and a true density of 0.2295 g / cm³ is finally obtained. 3 The yield of the low-density hollow glass microspheres was 46%, and the particle size D90 was 50 μm.
[0079] Comparative Example 4 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the composite foaming agent used in this comparative example is composed of calcium carbonate, sodium carbonate, sodium sulfate and sodium nitrate in a ratio of 6:1:1:1. The remaining steps and process parameters are the same, and the final true density is 0.2219 g / cm³. 3 The yield of the low-density hollow glass microspheres was 51%, and the particle size D90 was 57 μm.
[0080] Comparative Example 5 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the composite foaming agent used in this comparative example is composed of calcium carbonate, sodium carbonate, sodium sulfate and sodium nitrate in a ratio of 9:8:4:5. The remaining steps and process parameters are the same, and the final true density is 0.2170 g / cm³. 3 The yield of the low-density hollow glass microspheres was 56%, and the particle size D90 was 58 μm.
[0081] (2) Effect of silane-modified solution and its content
[0082] Comparative Example 6 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the coating and modification step, the mass ratio of aminopropyltriethoxysilane to alcohol in the silane modification solution is 1:4, and the silane modifier accounts for 0.2% of the mass of the glass powder; the remaining steps and process parameters are the same, and a true density of 0.2138 g / cm³ is finally obtained. 3 The yield of the low-density hollow glass microspheres was 61%, and the particle size D90 was 63 μm.
[0083] Comparative Example 7 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the coating and modification step, the mass ratio of aminopropyltriethoxysilane to alcohol in the silane modification solution is 1:2, and the silane modifier accounts for 1.0% of the mass of the glass powder; the remaining steps and process parameters are the same, and a true density of 0.2229 g / cm³ is finally obtained. 3 The yield of the low-density hollow glass microspheres was 75%, and the particle size D90 was 76 μm.
[0084] (3) Omit the silane modifier
[0085] Comparative Example 8 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the silane modifier aminopropyltriethoxysilane is omitted in the coating and modification step; the remaining steps and process parameters are the same, and a true density of 0.2201 g / cm³ is finally obtained. 3 The yield of the low-density hollow glass microspheres was 43%, and the particle size D90 was 68 μm.
[0086] (4) Omit the modification step
[0087] Comparative Example 9 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that in the coating and modification step, the steps of coating with the silane modifier aminopropyltriethoxysilane and the composite foaming agent are omitted; the remaining steps and process parameters are the same, and a true density of 0.2160 g / cm³ is finally obtained. 3 The yield of the low-density hollow glass microspheres was 29%, and the particle size D90 was 65 μm.
[0088] Table 1. Performance parameters of microspheres in Comparative Examples 6-9
[0089] Comparative Example 6 0.2138 63 7.8 9.3 61% Comparative Example 7 0.2229 76 6.9 9.6 75% Comparative Example 8 0.2301 68 7.3 9.4 43% Comparative Example 9 0.2160 65 7.2 9.3 29%
[0090] Based on Table 1, it can be seen from Example 1 and Comparative Examples 2-9 that the compounding modification of the composite foaming agent and silane coupling agent is beneficial to improving the yield of glass microspheres and effectively reducing the particle size of the microspheres.
[0091] III. Effects of Stirring and Drying
[0092] Comparative Example 10 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the stirring and drying method is not used in the coating and modification step; specifically, the microspheres are directly dried in an oven. The remaining steps and process parameters are the same, and a true density of 0.2332 g / cm³ is finally obtained. 3 The yield of low-density hollow glass microspheres was 70%, and the particle size D90 was 80 micrometers.
[0093] IV. The Influence of Wind Speed
[0094] Comparative Example 11 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the wind speed during high-temperature foaming and spherical formation is 20 m / s; the remaining steps and process parameters are the same, and the final true density is 0.2309 g / cm³. 3 The yield of low-density hollow glass microspheres was 75%, and the particle size D90 was 77 micrometers.
[0095] V. The impact of cleaning
[0096] Comparative Example 12 provides a low-density hollow glass microsphere and its preparation method, which is basically the same as the low-density hollow glass microsphere and its preparation method provided in Example 1. The main difference is that the washing process is omitted during the washing and sieving process; the remaining steps and process parameters are the same, and a true density of 0.2116 g / cm³ is finally obtained. 3 The finished low-density hollow glass microspheres have the following characteristics: compressive strength of 8.2 MPa, D90 of 51 μm, and pH of 10.4 when the volume breakage rate reaches 20%; and product yield of 81%. The performance parameters of the finished low-density hollow glass microspheres provided in this comparative example are shown in Table 2.
[0097] Table 2 shows the performance parameters of the microbeads provided in Comparative Example 12.
[0098] 0.2116 51 8.2 10.4 81%
[0099] The low-density hollow glass microspheres provided in Examples 1-3 and Comparative Example 12 were used to prepare polyurethane waterproof coatings by polyurethane in-situ polymerization. The experiment was repeated 10 times, and the statistical results of the 10 polymerization reaction processes are shown in Table 3.
[0100] The method for preparing polyurethane waterproof coating by in-situ polymerization includes: 600g of polyether diol 2000D, 10g of polyether triol YD3500, 350g of DOP, 20g of hollow glass microspheres, 5g of fumed silica, and 100g of nano-calcium carbonate are vacuum dehydrated for 2 h at 110℃ and -0.095MPa, then cooled to 70℃ and 260g of MDI is added. After reacting for 3 h, 0.5g of catalyst 101 is added to prepare a one-component polyurethane waterproof coating.
[0101] Table 3. Results of the application of low-density hollow glass microspheres in in-situ polymerization of polyurethane.
[0102] Example 1 No explosive polymerization occurred. There was one instance of high viscosity during testing, but this did not affect its usability. Example 2 No explosive polymerization occurred, and the reaction proceeded normally. Example 3 No explosive polymerization occurred, and the reaction proceeded normally. Comparative Example 12 Five burst polymerization events occurred, preventing the reaction from proceeding. Two tests showed high viscosity, but this did not affect usability.
[0103] As shown in Table 3, the low-density hollow glass microspheres of Examples 1-3, when applied to the in-situ polymerization of polyurethane, generally do not experience burst polymerization. Although Example 1 showed a high viscosity in one test, it did not affect its use and had little impact on the overall reaction. In contrast, Comparative Example 12 and Examples 2-3 showed normal in-situ polymerization reactions in every instance. With the addition of MDI, the probability of normal in-situ polymerization of the low-density hollow glass microspheres in Comparative Example 12 was 30%, the probability of burst polymerization was 50%, and the probability of high viscosity was 20%. The occurrence of burst polymerization prevents the formation of an effective polyurethane waterproof coating, thus increasing the production cost of the polyurethane waterproof coating.
[0104] In summary, the true density of low-density hollow glass microspheres produced in this embodiment of the invention, which involves high-temperature vitrification, modification, drying, followed by high-temperature sintering into spheres, washing, and sieving, is stably controlled between 0.2100 and 0.2500 g / cm³. 3 This technology enables precise control of microsphere density, uniform sphericity, high strength, and stable pH value, effectively solving problems such as large density fluctuations and uneven foaming in traditional processes. Moreover, low-density hollow glass microspheres have a high yield.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them; although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications can still be made to the specific implementation of the present invention or equivalent substitutions can be made to some technical features without departing from the spirit of the technical solutions of the present invention, and all such modifications and substitutions should be covered within the scope of the technical solutions claimed in the present invention.
Claims
1. A low-density hollow glass microsphere, characterized in that, True density 0.2100-0.2500 g / cm³ 3 The particle size D90 is not more than 55 μm, the pH is 7.0-9.5, and the compressive strength is not less than 8 MPa. The compressive strength refers to the pressure that the low-density glass microspheres are subjected to when the volume breakage rate reaches 20%.
2. The low-density hollow glass microspheres according to claim 1, characterized in that, The pH is 7.0-8.
5.
3. A method for preparing low-density hollow glass microspheres as described in claim 1 or 2, comprising the steps of: Raw material mixing and vitrification homogenization: First, the glass powder raw materials are uniformly mixed, then subjected to high-temperature melting and vitrification treatment, and then crushed and pulverized to obtain homogenized glass powder with a particle size D90 of 20-35μm; Coating modification: The homogenized glass powder is coated with a surface coating modifier to uniformly coat the surface of the homogenized glass powder, thereby obtaining modified glass powder; wherein, The surface coating modifier includes a composite foaming agent comprising 0.6-0.9% of the mass of the homogenized glass powder and a silane modifier comprising 0.3-0.8% of the mass of the homogenized glass powder. The composite foaming agent comprises calcium carbonate, sodium carbonate, sodium sulfate, and sodium nitrate in a mass ratio of 6-8: 5-8: 2-3: 2-3. High-temperature foaming into spheres: The modified glass powder is subjected to high-temperature foaming into spheres to obtain original hollow glass microspheres; Cleaning and sieving: The original hollow glass microspheres are first cleaned with a cleaning agent and then sieved to obtain the low-density hollow glass microsphere product; wherein, the cleaning agent is deionized water or an acid solution with a concentration of 2-3%.
4. The preparation method according to claim 3, characterized in that, In the steps of raw material mixing and vitrification homogenization, the high-temperature melting vitrification treatment method includes: melting and mixing uniformly mixed glass powder raw materials at 1400℃-1500℃ to form a transparent glass liquid with uniform composition and stable viscosity; and subjecting the glass liquid to water quenching and rapid cooling treatment to obtain glass clinker.
5. The preparation method according to claim 4, characterized in that, In the steps of raw material mixing and vitrification homogenization, the crushing and pulverizing process includes: coarsely crushing the glass cadmium to obtain coarse glass cadmium with a particle size of 200-300μm; and then using wet ball milling to obtain the vitrified homogenized powder.
6. The preparation method according to any one of claims 3-5, characterized in that, The glass powder raw materials, by weight, include: 60.0-70.0 parts quartz powder, 10-20 parts borax, 8-15 parts calcium carbonate, 10.0-15.0 parts sodium carbonate, 2.0-4.0 parts sodium sulfate, and 1.0-2.0 parts sodium nitrate.
7. The preparation method according to claim 6, characterized in that, The coating modification step includes: simultaneously spraying a silane modification solution and a composite foaming solution with a concentration of 20 wt%-25 wt% onto the glass powder under high-speed stirring at 800-1000 r / min, drying it, and obtaining modified glass powder with a water content of no more than 0.22%; wherein, the silane modification solution is prepared by uniformly mixing the silane modifier and alcohol at a mass ratio of 1:(3-5); the composite foaming solution is prepared by uniformly mixing the composite foaming agent and water.
8. The preparation method according to claim 7, characterized in that, The coating modification step includes: placing the glass powder in a high-speed disperser and stirring it; simultaneously spraying the silane modification solution and the composite foaming solution into the high-speed disperser at 85-95℃; after spraying, drying and stirring at 110-120℃ for 30-60 minutes to obtain the modified glass powder.
9. The preparation method according to claim 7 or 8, characterized in that, The silane modifier is at least one of aminopropyltrimethoxysilane, aminopropyltriethoxysilane, glycidoxypropyltrimethoxysilane, and glycidoxypropyltriethoxysilane.
10. The preparation method according to claim 7 or 8, characterized in that, The high-temperature foaming and spherical forming step includes: continuously feeding the modified glass powder into a high-temperature spherical forming furnace, and passing it through a flame at 1300-1400℃ at a speed of 30-50 m / s in an air atmosphere to form the original hollow glass microspheres.
11. The preparation method according to claim 10, characterized in that, The cleaning and sieving steps include: first, mixing and stirring the original hollow glass microspheres with the cleaning agent at a weight ratio of 1:5-7 for 30-60 minutes to make the pH of the hollow glass microsphere surface 7.0-9.5; then filtering and drying; and finally sieving to obtain the finished low-density hollow glass microspheres.
12. The application of the low-density hollow glass microspheres according to claim 1 or 2 in the preparation of polyurethane engineering materials.
13. The application according to claim 12, characterized in that, The application of low-density hollow glass microspheres as fillers in in-situ polymerization of polyurethane.